Effects of ecological factors and reproductive strategies on germination capability of Ailanthus altissima (Mill.) Swingle - Di Cocco, Alessandro; Panero, Ilaria; Fabrini, Giuseppe (Annali di Botanica, 2024)
The tree of heaven Ailanthus altissima is one of the most invasive plant species in Europe and Italy and poses a threat especially in urban environments. A deeper comprehension of how germination traits respond to environmental factors could help elucidate the process of invasion. Germination tests on A. altissima seeds collected at different altitudes were carried out at different light conditions (12-hr light/12-hr darkness and continuous darkness) and temperature regimes (15-6 °C, 20-10 °C and 25-15 °C). A further test was also performed to assess the germinative response of seeds retained on the plant during winter. Seeds have been demonstrated not to have clear preferences for temperature and light, nor to show an effect of the altitude at which they develop on their germination capacity. This characteristic makes A. altissima highly adaptable to different types of environments and not restrained to specifical conditions. Moreover, the continuous release of seeds throughout the year may maximize the chances of a successful germination. The nature of pioneer species of A. altissima emerges already during its reproduction and germination, both in its tolerance to different environmental conditions and in the adoption of a reproduction strategy oriented towards the extreme of r-strategist species, contributing to the invasiveness of the species.